Pengaruh Rasio Molar Umpan Terhadap Metanol Dan Waktu Reaksi Proses Pembuatan Biodiesel Menggunakan Membran Reaktor - Devi Indra Nengsih; Syarfi Syarfi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Indonesia is faced with an energy crisis fuel . This condition makes the business opportunity of biodiesel production is still promising . One of the technologies in generating alternative energy is the conversion of Jatropha oil into biodiesel using membrane reactor . This research aims to study the effect of variations in the molar ratio of castor oil with methanol to biodiesel conversion and the effect of reaction time on conversion , as well as studying the characteristics of biodiesel produced . The process of making biodiesel using membrane reactor polypropilen pore size of 0.1 lm diameter with a maximum temperature of 55 º C and a maximum pressure of 1 bar . Variation is the molar ratio of 1:10, 1:15 and 1:20 and the time variation of 1 , 2 and 3 hours . The highest biodiesel yield at a ratio of 1:20 was 97.35 % at the reaction time of 1 hour . Results Characterization of physical properties of blends of biodiesel which meets the quality standards of the kinematic viscosity of biodiesel ranges between 4.01-4,24 cSt and biodiesel ranges 0874-0883 g/cm3 density and acidity rate ranged between 0.56-0.71 mg KOH / g sample . Molar variation affects the quality of the biodiesel produced is at a molar ratio of 1:20 .  Keywords : Biodiesel , Membrane Reactor , molar ratio , reaction time.